1998
DOI: 10.1017/s0022112098002341
|View full text |Cite
|
Sign up to set email alerts
|

On the characteristics of vortex filaments in isotropic turbulence

Abstract: The statistical properties of the strong coherent vortices observed in numerical simulations of isotropic turbulence are studied. When compiled at axial vorticity levels ω/ω′∼Re1/2λ, where ω′ is the r.m.s. vorticity magnitude for the flow as a whole, they have radii of the order of the Kolmogorov scale and internal velocity differences of the order of the r.m.s. velocity of the flow u′. Theoretical arguments are given to explain these scalings. It is shown that the filaments are inhomogeneous Burg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
201
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(237 citation statements)
references
References 42 publications
33
201
1
2
Order By: Relevance
“…The inner dimension of vortex clusters in figure 6(d) is r 1 ≈ 6η, independently of the cluster volume, which approximately agrees with the diameter of individual filamentary vortices in turbulence (Jiménez & Wray 1998;Tanahashi, Iwase & Miyauchi 2001;del Álamo et al 2006;Pirozzoli, Bernardini & Grasso 2008;Stanislas, Perret & Foucaut 2008). It is also consistent with the description of vortex clusters as 'sponges of strings' (LFJ12).…”
Section: Flow Anisotropysupporting
confidence: 82%
“…The inner dimension of vortex clusters in figure 6(d) is r 1 ≈ 6η, independently of the cluster volume, which approximately agrees with the diameter of individual filamentary vortices in turbulence (Jiménez & Wray 1998;Tanahashi, Iwase & Miyauchi 2001;del Álamo et al 2006;Pirozzoli, Bernardini & Grasso 2008;Stanislas, Perret & Foucaut 2008). It is also consistent with the description of vortex clusters as 'sponges of strings' (LFJ12).…”
Section: Flow Anisotropysupporting
confidence: 82%
“…This is because these vortices are undergoing significant distortion [14] and are unlike equilibrium Burgers vortices which have been proposed as a generic model (e.g. [26]). The intense small-scale velocity fluctuations induced by the vortices are probably associated with the small-scale 'nibbling process' that determines the boundary entrainment velocity, E b [27].…”
Section: Boundary Interface Dynamicsmentioning
confidence: 99%
“…They observed that at the beginning of the merging, two strong filaments of vorticity are ejected, and roll up around the final vortex due to the differential rotation, leading to an axisymmetric vortex at late stages. Just as in previous work by Kevlahan and Farge (1997), Elhmaidi et al (2004), Dritschel (1989), Jimenez et al (1993), Jimenez and Wray (1998), Meunier et al (2005) and Petitjeans (2003), narrow strips of intense vorticity are what is meant when referring to 'vorticity filaments' in this work. However, as pointed out by (Petitjeans 2003), the presence of vorticity does not imply the existence of a vortex, e.g.…”
Section: R Mukaromentioning
confidence: 71%
“…The same objects have been identified by locating local minima of pressure fields in numerical experiments (Belin et al 1996). Dritschel et al (1991) noted that a common feature of strongly non-linear, high Reynolds number, two-dimensional flows is the presence of thin filaments of vorticity, while Jimenez and Wray (1998) also observed that most of the strong vorticity in the flow field is in the form of filaments. According to Elhmaidi et al (2004), vorticity filaments are easily generated during vortex-vortex interactions (such as vortex merger), and when vortices are exposed to strong shearing.…”
Section: R Mukaromentioning
confidence: 77%
See 1 more Smart Citation